Medication Adherence and Treatment Patterns for Hypogonadal Patients Treated with Topical Testosterone Therapy: A Retrospective Medical Claims Analysis. (6th March 2013) - Schoenfeld, Michael Jay; Shortridge, Emily; Cui, Zhanglin; Muram, David
Abstract Introduction There is limited information on adherence to topical testosterone replacement therapy (TRT) among hypogonadal men. Aim To determine adherence rates among men treated with topical testosterone gels and to examine factors that may influence adherence, including age, presence of a specific diagnosis, and index dose. Methods Included were 15, 435 hypogonadal men, from the Thomson Reuters MarketScan® Database, who had an initial topical testosterone prescription in 2009 and who were followed for 12 months. Main Outcome Measures Adherence to testosterone was measured by medication possession ratio (MPR), with high adherence defined as ≥0.8. Persistence was defined as the duration of therapy from the index date to the earliest of the following events: end date of the last prescription, date of the first gap of >30 days between prescriptions, or end of the study period (12 months). Results Adherence to topical TRT was low. By 6 months, only 34.7% of patients had continued on medication; at 12 months, only 15.4%. Adherence rates were numerically similar among men who received AndroGel® or Testim® topical gels and did not differ among men of different age groups. Approximately 80% of patients initiated at the recommended dose of 50 mg/day. Over time, an increased proportion of men used a higher dose. This change was the result of dose escalation, rather than of greater adherence among men initiating therapy at a high dose. Dose escalation was seen as early as 1 month into therapy. Approximately 50% of men who discontinued treatment resumed therapy; most men used the same medication and dose. Conclusions Discontinuation rates are high among hypogonadal men treated with testosterone gels, irrespective of their age, diagnosis, and index dose. Further study, evaluating other measurable factors associated with low adherence among patients receiving topical TRT, may lead to interventions designed to improve adherence with therapy.